Hubungan Jumlah Kendaraan Bermotor Dengan Kadar Karbon Monoksida (CO) Di Udara Pada Jalan Depan Pasar Bandar Buat Kota Padang - Muslim, Burhan; Dahliati, Geni; Suksmerri, Suksmerri; Irfan, Asep; Adriyanti, Sri Lestari; Sugriarta, Evino (Sulolipu: Media Komunikasi Sivitas Akademika dan Masyarakat, 2024)
Carbon monoxide (CO) is a poisonous gas that is commonly found in urban areas. Carbon monoxide levels in the air are influenced by many factors, including the number of motorized vehicles, climatic factors, geography, and activities that burn fuel containing carbon. This research aims to determine the relationship between the number of motorized vehicles and CO levels in the air on Jalan Front Pasar Bandar Buat, Padang City in 2023. This research is a correlational study with a cross-sectional approach carried out in August 2023. The dependent variable of this research is the measured CO levels in the air. every hour for 8 hours, while the independent variable is the number of motorized vehicles passing the road in front of Pasar Bandar Buat, Padang City. Analyze the results to see the relationship between the independent variable and the dependent variable using correlation analysis. The average number of motorized vehicles passing on the road in front of Bandar Buat Market on weekdays is 3,384 vehicles/hour, while on holidays it is 4,080 vehicles/hour. The climatic factor conditions during the research were within the normal range for Padang City. Carbon monoxide levels on the road in front of Bandar Buat Market on holidays are higher, namely 3,136 µg/Nm3 and on weekdays 2,554 µg/Nm3. The results of the analysis show that Carbon Monoxide levels are positively correlated with the number of motorized vehicles with a value of r = 0.9. This research recommends increasing the quantity and quality of public transportation, to reduce the use of private vehicles in society  Keyword: Air Pollution; Carbon Monoxide; Motorized Vehicles